Study of Significant Relationship between Determination of Parenting Patterns to Accuracy Stages Preschool Child Development - Tria Wahyuningrum; Lida Khalimatus Sa'diya (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Children aged preschool (48–72 months ) experience phase very rapid growth and development . One of them factor significant external influence this process is pattern parenting . This research aim For analyze connection between pattern foster parents with development child age preschool at PAUD Al Izzah Puri Mojokerto, Mojokerto Regency . The research method used is quantitative with design analytic correlational through approach cross-sectional . Population study includes 65 children preschool , with sample A total of 55 respondents were taken use technique purposive sampling . Instrument study covering Parenting Styles and Dimensions Questionnaire (PSDQ) for measure pattern foster care and questionnaire Pre - Developmental Screening (KPSP) for evaluate development children . Research results show that majority of parents apply pattern foster care democratic (82.4%) and partly big development child is in the category according (88.2%). Statistical test Spearman's Rho show mark p-value = 0.000 (< 0.05) with coefficient correlation (r) of 0.568. This is show existence connection significant positive with strength currently between pattern parenting and development children . Parents recommended For Keep going consistent apply pattern supportive care stimulation aspect motor skills , language , and independence child